A TaqMan® multiplex assay for hoofed livestock species identification and nuclear DNA quantification - Premasuthan, A. (2017)
We have developed a TaqMan® real-time quantitative PCR (qPCR) multiplex assay that identifies and quantifies minute amounts (0.5 – 5 pg) of mixed-species nuclear DNA of cattle (Bos taurus), horse (Equus caballus), goat (Capra hircus)/sheep (Ovis aries), and pig (Sus scrofa) in a species-specific manner. The assay’s ability to accurately detect and quantify target DNA in multi-species mixtures is crucial when the target specimen may be overwhelmed by non-target specimen. We have evaluated the assay using simulated forensic sample conditions and demonstrated that this assay is applicable for investigating criminal and civil cases including meat authentication and agri-food testing to ensure health and safety. The efficient determination of the species of origin of biological material and the accurate quantification of the species-specific template DNA will help reduce the potential risks that fraudulent/imitation and contaminated food products could pose to our food supply. Our assay’s ability to accurately identify and quantify species-specific DNA present in biological samples will also facilitate downstream analyses that generate DNA profiles of the specimen for genetic identity testing and traceability. This TaqMan® qPCR assay will facilitate meat inspectors, regulatory agencies, and food safety and quality control laboratories to enforce accurate labeling of livestock meat products and prevent fraudulent manipulations of our food supply.